Aproveitamento da água da chuva após tratamento por filtração ascendente e radiação ultravioleta - Silva, Felipe Amaral (2015)
The scarcity, quality deterioration of water sources and increasing demand for water has been global problem. Faced with these problems the use of alternative sources is cited as a solution, especially taking advantage of rainwater. In some places, rainwater drained roofs have been used for potable and non-potable purposes and rainwater in nature has superior quality to the surface water and groundwater. Although rainwater has physicochemical quality within the potability standards, it is necessary to improve their quality to use it. Thus this work is evaluated treatment of rainwater by upflow filter (35,4 L volume) with support means of 0,50 m of Boulder and filter layer of 0,15 m of crushed stone, 0,25 m of sand and 0,55 m of activated carbon and UV disinfection. To enhance the water quality before reaching the filter was installed a first-flush device with volume of 41,4 L. The characterization of the water before and after treatment was performed through analysis of parameters pH, temperature, color, dissolved oxygen, turbidity, ammonia, nitrite, nitrate, phosphate, sulphate, COD and coliforms. The mean values obtained for the physicochemical parameters of the water after treatment were 6,7 to pH 22,3 °C for temperature, 12,5 UPC for color, 6,7 mg/L to OD, 0,5 NTU for turbidity, 0,2mg/L for ammonia, 0,01 mg/L for nitrite, 1,7 mg/L for nitrate, 0,2 mg/L for phosphate,0,7 mg/L for sulfate and 1,3 mg/L for COD. The obtained results proposed treatment for color removal efficiency of 22,4%, haze 28,6%, 50,0% ammonia, 23,1% nitrite, nitrate 37,0%, Phosphate 95,1%, sulfate 41,7% and COD of 66,7% and reduced the number of microorganisms to a value less than the detectable limit of the analysis method. All mean values obtained for the physicochemical parameters meet the standards required by the Order 2914/2011 of the Ministry of Health for drinking water.